2003
DOI: 10.1108/10222529200300011
|View full text |Cite
|
Sign up to set email alerts
|

Cash flow reporting: Do listed companies comply with AC 118?

Abstract: This article assesses the state of cash flow reporting by listed South African industrial companies in order to evaluate whether the users of financial statements can accept them as being reliable and use them as a tool to compare the operating performance of various companies. As the cash flow statement has been in use since 1989, it was envisaged that compliance would be high. However, it was found that there are several companies that deviate from some of the requirements of AC 118 regarding cash flow state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…During the 2001 financial year, 41% of the industrial companies that were listed in South Africa provided some form of information on this allocation (Steyn and Hamman 2003a). The separation should therefore be possible, even if it is somewhat subjective.…”
Section: Mandatory Cash Utilisation and Maintenance Of The Existing Resource Basementioning
confidence: 99%
See 2 more Smart Citations
“…During the 2001 financial year, 41% of the industrial companies that were listed in South Africa provided some form of information on this allocation (Steyn and Hamman 2003a). The separation should therefore be possible, even if it is somewhat subjective.…”
Section: Mandatory Cash Utilisation and Maintenance Of The Existing Resource Basementioning
confidence: 99%
“…It is already obligatory for the cash flows from discontinued activities to be disclosed separately. However only 21 of 60 industrial companies listed in South Africa that discontinued operations did disclose the necessary information in their 2001 financial statements (Steyn and Hamman 2003a). Buckley (1977) also promotes the disclosure of divisional and geographical cash flow segmentation, because users apply different discount rates to different divisions to estimate future cash flow.…”
Section: Discontinued Operations and Other Allocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the 2001 published cash flow statements of South African listed industrial companies(Steyn & Hamman 2003), it was found that only 26 of 287 companies reported…”
mentioning
confidence: 99%